2021
DOI: 10.1002/bies.202000288
|View full text |Cite
|
Sign up to set email alerts
|

Early life exposure to air pollution impacts neuronal and glial cell function leading to impaired neurodevelopment

Abstract: The World Health Organisation recently listed air pollution as the most significant threat to human health. Air pollution comprises particulate matter (PM), metals, black carbon and gases such as ozone (O 3 ), nitrogen dioxide (NO 2 ) and carbon monoxide (CO). In addition to respiratory and cardiovascular disease, PM exposure is linked with increased risk of neurodegeneration as well as neurodevelopmental impairments.Critically, studies suggest that PM crosses the placenta, making direct in utero exposure a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 110 publications
(204 reference statements)
1
17
0
Order By: Relevance
“…Activation of microglia following exposure to air pollution is a recognized outcome in both cell studies and animal models (reviewed in [26]). Indeed, microglia activation by PM can be direct (inhaled nasally, bypassing the BBB) or through systemic inflammation (via the respiratory system [46]).…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of microglia following exposure to air pollution is a recognized outcome in both cell studies and animal models (reviewed in [26]). Indeed, microglia activation by PM can be direct (inhaled nasally, bypassing the BBB) or through systemic inflammation (via the respiratory system [46]).…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…However, we found that in measures of cytotoxicity, ROS gen- eration and proinflammatory response were greater in BV2 cells than in C17.2 cells following exposure to UPM. Activation of microglia following exposure to air pollution is a recognized outcome in both cell studies and animal models (reviewed in [26]). Indeed, microglia activation by PM can be direct (inhaled nasally, bypassing the BBB) or through systemic inflammation (via the respiratory system [46]).…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Fifth, in addition to the old age, early life (during pregancy and early childhood) is another sensitive period of cognitive impairment, and it remains to be determined whether air pollution abatement in early life could result in longterm improvement of cognitive function. 8 Air pollution has been considered the single largest environmental threat for human health, and the disease burden related to air pollution has been estimated to be on a par with other common behavioural risk factors in predicting future health. 9 The work by Yao and colleagues 3 strengthens the scientific evidence for a link between air pollution and cognitive decline.…”
Section: Preventing Cognitive Impairment By Reducing Air Pollutionmentioning
confidence: 99%
“…For example, particulate matter of small diameter such as PM1 or PM2.5 might initiate oxidative stress and lead to the formation of inflammatory cytokines that infiltrate the blood-brain barrier causing neurodegeneration and neuroinflammation [ 11 ]. Specifically, exposure to ambient PM2.5 results in depressive responses and increased hippocampal pro-inflammatory cytokines [ 11 ], while exposure to PM1 leads to increased inflammation and reactive oxygen species (ROS) generation and impacts learning and memory [ 12 ]. In this context, traffic related air pollution (e.g., particulate matter and NO 2 ) have been linked by observational research to increased rates of mental health problems including: autism spectrum disorders [ 13 ], schizophrenia [ 14 ], dementia [ 15 ], psychotic experiences [ 16 , 17 ], cognitive disabilities [ 18 ], anxiety and major depressive disorders [ 19 ].…”
Section: Introductionmentioning
confidence: 99%